(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Annotation: This article develops a system of exercises aimed at developing independent learning skills in computer science lessons for schoolchildren. The exercises are organized step-by-step and are aimed at developing the competencies of algorithmic thinking, problem solving, and independent work. The effectiveness of the system is justified from a pedagogical point of view.